2016
DOI: 10.3126/mjsbh.v15i1.15188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycopyrolate on Nausea, Vomiting and Neonatal Outcome During Spinal Anaesthesia for Elective Caesarean Section

Abstract: Introduction: Glycopyrrolate has better antisialagogue effect and does not cross placental barrier; thereby when given immediately before subarachnoid block for elective caesarean section might reduce incidence and severity of nausea and vomiting without affecting neonatal outcome. Methods: In a prospective randomized double blind placebo controlled study, sixty ASA PS I and II patients undergoing elective caesarean section at term were assigned to receive 1 ml of Inj Normal Saline IV or 1 ml (0.2 mg) of Inj G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
1
1
Order By: Relevance
“…5,7 In the present study, there was no significant difference in nausea and vomiting but a significant difference in the dry mouth between the two groups which was similar to some studies. 4,9,21 In the present study dry mouth was more in the glycopyrrolate group which was statistically significant but another study showed no evidence of dryness of mouth in any of the study patients. 7 Numerous endocrinal, systemic, and physiological alterations can occur during pregnancy.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…5,7 In the present study, there was no significant difference in nausea and vomiting but a significant difference in the dry mouth between the two groups which was similar to some studies. 4,9,21 In the present study dry mouth was more in the glycopyrrolate group which was statistically significant but another study showed no evidence of dryness of mouth in any of the study patients. 7 Numerous endocrinal, systemic, and physiological alterations can occur during pregnancy.…”
Section: Discussioncontrasting
confidence: 55%
“…5,20 Glycopyrrolate also possess antiemetic properties by inhibiting central muscarinic and cholinergic emetic receptors. 21 It has been reported that glycopyrrolate minimizes the incidence of nausea vomiting during spinal anesthesia for caesarean section without affecting fetal outcome. 5,7 In the present study, there was no significant difference in nausea and vomiting but a significant difference in the dry mouth between the two groups which was similar to some studies.…”
Section: Discussionmentioning
confidence: 99%